Corporate governance and performance of company stocks in the consumer and retail sector - Rocha, Guilherme André Peleglini; Contani, Eduardo Augusto do Rosário; Reco, Thais Lucimara da Silva (Contextus - Revista Contemporânea de Economia e Gestão, 2018)
This article analyses the correlation between corporate governance (CG) and stock performance, with the purpose of assessing the degree to which the classification of CG levels (N1, N2 and NM) and the behavior of stock exchange shares in the consumer and retail sector as listed in B3 (Brazil, Stock, Counter) can be mutually influenced. A quantitative methodological approach was used, drawn from the statistics obtained through t and F tests, to find possible differences with respect to risk and return between the group with CG and the traditional one. Three research hypotheses were raised in order to compare: (i) return of shares of companies with CG in contrast to that of companies listed in the traditional segment, (ii) return of shares of companies with CG and of those listed in Ibovespa and (iii) risk of companies with CG and of those listed in the traditional segment. It has been found that companies listed with CG do not present statistically superior returns to traditional companies, which is a result that was also found in other studies (BAMPI et al., 2009; DOMINGOS; MOURA, 2015). On the other hand, companies with CG have less risk when compared to the companies listed in the traditional segment, thus confirming one of the research hypoteses and corroborating the findings of Matucheski, Clemente and Sandrini (2009) and Da Silva, Nardi and Junior (2012). There has also been no statistically significant difference between the companies with CG and the Ibovespa, a result also found in De Alencar et al. (2012).